2017
DOI: 10.5483/bmbrep.2017.50.8.097
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β1 enhances adhesion of endometrial cells to mesothelium by regulating integrin expression

Abstract: Endometriosis is the abnormal growth of endometrial cells outside the uterus, causing pelvic pain and infertility. Furthermore, adhesion of endometrial tissue fragments to pelvic mesothelium is required for the initial step of endometriosis formation outside uterus. TGF-β1 and adhesion molecules importantly function for adhesion of endometrial tissue fragments to mesothelium outside uterus. However, the function of TGF-β1 on the regulation of adhesion molecule expression for adhesion of endometrial tissue frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…TGF-β1 has been shown to increase the adhesion of endometrial stromal cells in vitro in parallel with increased expression of α5, αV, β3 and β5 integrins in ectopic endometrium in endometriosis patients compared to entopic endometrium. This is consistent with other work suggesting increased integrin expression via the TGFβ-1/Smad2 signalling pathway [ 28 ]. Increased entopic endometrial mRNA levels of αV integrin and αVβ3 integrins have also been shown in women with endometriosis as compared to healthy controls, which occurs in conjunction with increased peritoneal IL-1β mRNA levels [ 29 ].…”
Section: Integrins- Role In Endometriotic Lesions and Subfertilitysupporting
confidence: 93%
“…TGF-β1 has been shown to increase the adhesion of endometrial stromal cells in vitro in parallel with increased expression of α5, αV, β3 and β5 integrins in ectopic endometrium in endometriosis patients compared to entopic endometrium. This is consistent with other work suggesting increased integrin expression via the TGFβ-1/Smad2 signalling pathway [ 28 ]. Increased entopic endometrial mRNA levels of αV integrin and αVβ3 integrins have also been shown in women with endometriosis as compared to healthy controls, which occurs in conjunction with increased peritoneal IL-1β mRNA levels [ 29 ].…”
Section: Integrins- Role In Endometriotic Lesions and Subfertilitysupporting
confidence: 93%
“…It is well known that epithelial-mesenchymal transition (EMT), one of the most important mechanisms of fibrotic diseases, has recently been considered to be intimately involved in the pathogenesis of endometrial fibrosis ( 9 , 10 ). Transforming growth factor β1 (TGF-β1), an archetypical pro-inflammation and fibrosis cytokine, is related to biological processes including inflammatory activity, cell adhesion, and EMT progress ( 11 ). Previous studies reported that the mesenchymal marker vimentin is increased while epithelial marker E-cadherin is decreased in injured endometrium of IUA animal model ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…TGF‐β1 has been shown to regulate several integrins including αV, β1 and β3 in glioblastoma, fibroblast and kidney epithelial cells . Others have suggested that the positive regulation of integrin αV, α6, β1 and β4 by TGF‐β1 signalling is probably mediated via the activation of the TGF‐β1/TGF‐βRI/Smad2 signalling pathway . Furthermore, the TGF‐β1‐mediated Smad signalling pathway has been shown to play an important role in EMT associated with metastatic progression .…”
Section: Introductionmentioning
confidence: 99%
“…14 Others have suggested that the positive regulation of integrin αV, α6, β1 and β4 by TGF-β1 signalling is probably mediated via the activation of the TGF-β1/TGF-βRI/Smad2 signalling pathway. 15 Furthermore, the TGF-β1-mediated Smad signalling pathway has been shown to play an important role in EMT associated with metastatic progression. 10 A study by Hung et al has also reported that TGF-β1 induces Cten upregulation in a dose-dependent manner and FGF2 mediates Cten-induced motility; however, the role of Cten in TGF-β1-mediated EMT and motility was not explored.…”
Section: Introductionmentioning
confidence: 99%